Mga palasyo ni Erap a compilation of investigative reports on the Erap mansions - Mangahas, Malou (Philippine Center for Investigative Journalism, 2000)
A documentary by the Philippine Center for Investigative Journalism, with the Probe Team and The Correspondents, on the houses owned, occupied or frequented by former President Joseph Estrada and his families, numbering at least 17 pieces of choice property worth over P2 billion in Metro Manila, Baguio and Tagaytay.